Effect of traditional Chinese exercise on abnormal lipid metabolism in patients with atherosclerosis: a protocol for meta-analysis of randomised controlled trials - Chen Wang; Peizhen Zhang; Yuting Yang (BMJ Open)
Introduction Atherosclerosis (AS) is an abnormal response within the vessel wall to endothelial dysfunction and inflammatory cellular processes. Taijiquan exercise as a moderate-intensity aerobic exercise can control or reverse AS by gradually reducing the deposition of cholesterol on the walls of blood vessels. Similarly, performing Baduanjin exercise, Liuzijue Qigong, Wuqinxi exercise and Yijinjing exercise has been found to have a positive effect on lipid metabolism in patients with AS. However, these studies focused only on middle-aged and older populations over 50 years of age and had short intervention periods, poor quality control and patient compliance, and no stratification by age and gender to observe the effects of traditional Chinese exercise (TCE) on patients with AS. Therefore, this meta-analysis will explore the specific effects of different TCE interventions on lipid metabolism in patients with AS through subgroup analysis of factors such as age, gender, intervention cycle and training method and lay the foundation of evidence-based medicine for the promotion of TCE in both clinical practice and the community.Methods and analysis A systematic approach will be completed to search the literature published up to 30 September 2021 in the following databases: Web of Science, PubMed, Embase, Cochrane Library, EBSCO and CNKI. Other databases will also be searched manually. Lipid metabolism is the primary outcome indicator. Data synthesis, sensitivity analysis, regression analysis, subgroup analysis and risk bias evaluation will be performed using RevMan V.5.3 software. In addition, funnel plots generated by Begg’s and Egger’s tests will be used to assess reporting bias.Ethics and dissemination Ethical approval and consent are not necessary as no primary data will be collected. The results of the study will be disseminated through carefully reviewed publications.PROSPERO registration number CRD42022304283.